Three Cornered Moon [cast and crew] (1934)
Beverly Hills High School Playbill for the Senior Class of W '34 in 'A Merry, Mad, Modern Comedy' by Gertrude Tonkonogy featuring Winnifred Smith (the future Mrs. Cody) as Jenny and William F. Cody as the Set Designer.